Scaling species richness and endemism of tropical dry forests on oceanic islands. Issue 8 (19th January 2013) - Gillespie, Thomas W.; Keppel, Gunnar; Pau, Stephanie; Price, Jonathan P.; Jaffré, Tanguy; O'Neill, Kristin; Huston, Michael
Abstract Aim We examine variation in woody plant species richness and endemism within tropical dry forest on oceanic islands and determine what climatic and biogeographic metrics best explain native species richness and endemism across archipelagos, islands and plots. Location Oceanic islands in the Pacific. Methods Stand‐level sampling (0.1 ha) at 35 different dry forest sites across 16 islands, and five archipelagos (New Caledonia, Fiji, Marquesas, Marianas and Hawaii). Descriptors of native species richness and endemism were calculated at the plot, island and archipelago level. Biogeographic and climate metrics at the archipelago, island and plot level were drawn from the literature and computer databases. The effects of biogeographic and climate metrics were investigated using linear mixed‐effects models. Results Dry forests of New Caledonia and Fiji had the highest native species richness, while New Caledonia and Hawaii had the highest endemism. Native species richness and endemism within tropical dry forests on oceanic islands are primarily influenced by biogeographic metrics, especially isolation of the archipelago, and not climatic metrics. Most variance in native species richness and endemism (60% and 64%) is at the archipelago level compared with the island (8%, 16%) and plot (32%, 15%) level. At the island level, species richness in tropical dry forest is affected by precipitation, while island area significantly affects endemism. The area of forest fragments is an important predictor of native species richness and endemism in plots. Main conclusions Although dry forests in the Pacific have been exceptionally deforested and degraded, high native species richness and endemism remains in a number of forest fragments. Biogeographic metrics explain most of the variance in native species richness and endemism across scales, while climatic metrics are important at the island level. First‐order assessments of native richness and endemism at the archipelago, island and stand‐level are possible for forest types on oceanic archipelagos.